Metazoan parasites in the head region of the bullet tuna Auxisrochei (Osteichthyes: Scombridae) from the western Mediterranean Sea. Issue 6 (November 2015) - Mele, S.; Saber, S.; Gómez-Vives, M.J.; Garippa, G.; Alemany, F.; Macías, D.; Merella, P.
Abstract The head region of 72 bullet tuna Auxis rochei from the western Mediterranean Sea (south-east Spain and the Strait of Gibraltar) was examined for parasites. Seven metazoan species were found in the fish from south-east Spain: three monogeneans, two trematodes and two copepods, whereas only three species were isolated in the fish from the Strait of Gibraltar. A comparison of the levels of infection of the parasites according to fish size in south-east Spain showed that the prevalence of Didymozoon auxis and the mean abundance of Allopseudaxine macrova were higher in the larger hosts (range of fork length = 38–44 cm) than in the smaller ones (33–37 cm). A comparison of the parasite infections according to geographical region showed that the mean abundances of Nematobothriinae gen. sp. and Caligus bonito were higher in fish from south-east Spain than in those from the Strait of Gibraltar. A comparison of the parasite fauna of A. rochei from the Mediterranean Sea with the published data on Auxis spp. from the Atlantic, Indian and Pacific Oceans revealed the closest similarity between the Mediterranean A. rochei and the Atlantic A. thazard.